OPERATIONAL CONCEPT OF ARRIVAL MANAGER - Luppo, Oleksandr; Argunov, Gennadiy; Golyash, Oleksandr (Proceedings of National Aviation University (archive), 2016)
In this article is analyzed the conceptual structure of AMAN, namely the topicality and history of creation ofthis conception, principles and availability for usage of this concept for the purpose of improvement of air traffic control.We reviewed ways of AMAN usage on examples of arrival and departure aircraft and determined major advantages andnecessity of conception implementation.